Forest management in Bolivian indigenous territories - Recommendations for CSOs - Ascarrunz, N., Angulo, A.R., Serrano, A.B., Benneker, C. (2020)
As part of a multi-country review of community forest rights, the Instituto Boliviano de Investigación Forestal (IBIF) conducted a review of three of Bolivia’s indigenous territories—Monteverde, Lomerío, and Guarayos. We focussed on: (i) the outcomes of this collective tenure model in terms of livelihoods and forest conservation; (ii) the conditions and constraints for achieving positive outcomes; and (iii) the potential role of CSOs in improving the outcomes. In this policy brief we summarize some of the main outcomes of the review, and the consequent recommendations for CSOs.